2011
DOI: 10.1158/0008-5472.can-10-2380
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 Inhibition Is a Therapeutic Strategy for ABC-like Diffuse Large B-Cell Lymphoma

Abstract: Persistent STAT3 signaling contributes to malignant progression in many diverse types of human cancer. STAT3 is constitutively active in activated B cell (ABC)-like diffuse large B cell lymphomas (DLBCL), a class of non-germinal center derived DLBCL cells for which existing therapy is weakly effective. In this report, we provide a preclinical proof of concept that STAT3 is an effective molecular target for ABC-like DLBCL therapy. Direct inhibition of STAT3 with shRNA suppressed the growth of human ABC-like DLB… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 17 publications
6
83
0
2
Order By: Relevance
“…In contrast, Stat3 is constitutively active in cancer cells, resulting in dampened immune responses and leading to tumor evasion. In accord with previous reports on melanoma, colon carcinoma, sarcoma, and diffuse large B cell lymphoma cell lines (6,26,27) (28). In line with this evidence, in this work, we demonstrated that DCs from mice immunized with Stat3Y705F-C4HD cells cocultivated with C4HD cells were able to upregulate CD86 and MHC class II molecules, markers of DC maturation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, Stat3 is constitutively active in cancer cells, resulting in dampened immune responses and leading to tumor evasion. In accord with previous reports on melanoma, colon carcinoma, sarcoma, and diffuse large B cell lymphoma cell lines (6,26,27) (28). In line with this evidence, in this work, we demonstrated that DCs from mice immunized with Stat3Y705F-C4HD cells cocultivated with C4HD cells were able to upregulate CD86 and MHC class II molecules, markers of DC maturation.…”
Section: Discussionsupporting
confidence: 93%
“…These approaches, which include in vivo blocking of Stat3 by using genetic deletions in tumor cells or in tumor-infiltrating immune cells or by administration of pharmacological inhibitors, have variable rates of success in stimulating antitumor immune responses (5,27,40,41); however, both of these approaches have limited clinical application until targetspecific delivery is possible. To our knowledge, our study provides the first report of the use of ex vivo Stat3-inactivated tumor cells as an immunotherapy; this approach has the advantage of immunizing the host with the whole array of Ags expressed by the tumor cells in a stimulatory microenvironment composed of multiple proinflammatory cytokines and chemokines to generate an antitumor immune response.…”
Section: Discussionmentioning
confidence: 99%
“…3c), an effect that has also been reported for human ABC-like diffuse large B-cell lymphomas 24 . When Em-Myc lymphoma-challenged mice were treated for six consecutive days with JSI-124, a delayed clinical disease progression was seen.…”
Section: Progression Of a Myc-driven B-cell Lymphoma Depends On Dcssupporting
confidence: 63%
“…We used 2 cell-permeable SH2 domain-targeting STAT3 inhibitors, STAT3 inhibitor V (Stattic) and STAT3 inhibitor VI (S3I-201), which have previously been shown to specifically inhibit cellular STAT3 phosphorylation. [23][24][25] Treatment of primary CD34 ϩ BM-MNCs with these inhibitors resulted in reduced levels of phospho-STAT3 (pSTAT3; Figure 4E). Compared with DMSOtreated cells, pSTAT3 levels were reduced by 2.5-fold (59%) and by 16.4-fold (94%) on treatment with STAT3 inhibitor V and STAT3 inhibitor VI, respectively ( Figure 4E).…”
Section: Expression Profiling Reveals Transcriptional Alterations Andmentioning
confidence: 99%